The Asymmetric Incidence of Business Taxes: Survey Evidence from German Firms - Richard Winter; Philipp Doerrenberg; Fabian Eble; Davud Rostam-Afschar; Johannes Voget (Institute of Labor Economics (IZA), 2025)
We provide novel evidence on the incidence of business taxes using comprehensive survey and experimental data from German firms. Leveraging randomized variation in hypothetical tax changes, we find that the incidence of profit taxes is highly asymmetric. Tax decreases are more likely to benefit workers and stimulate investment, whereas tax increases tend to be passed on to consumers through higher prices and absorbed by firm owners through reduced profit distributions. Moreover, by varying the magnitude of the tax changes, we demonstrate that worker incidence increases with the absolute size of the tax change, partially offsetting the burden on firm owners.
Keywords: D22; H00; H22; H25; J23; J30; 330; investment; firm behavior; tax incidence; corporate tax; payout; wages